Are same-sex relationships anti-family?: Investigating relationship stability among interracial gay partners in South Africa - Adeagbo, Oluwafemi Atanda (Journal of gender studies, 2018)
One of the main heteronormative beliefs, especially in South Africa, is that same-sex partners do not enjoy stable relationships and that their relationships are often consciously short-term and lack enduring forms of commitment. The last three decades have witnessed the production of some studies (mostly in Europe and America) on same-sex intimate relationships and familial arrangements. Most of these studies compared same-sex and heterosexual relationships. Past studies found some similarities between love and satisfaction in heterosexual and same-sex intimate relationships. In this regard, this study examined relationships stability and satisfaction ingredients among interracial gay partners living in selected Johannesburg suburbs. This study is based on an eight-month qualitative study among 10 interracial gay partners living in some selected Johannesburg suburbs. Data were collected through in-depth interviews from 10 interracial gay men (comprising 20 men who are between 23 and 58 years at the time of the research) in intimate relationships. This study finds that relationship stability and satisfaction was linked to effective communication, trust and equity as the main elements of the interracial gay partnerships. Gay men in this study have similar desires for close intimate bonds and stable households - and adopt numerous resilience strategies to ensure that these relationships remain intact. This contradicts the general stereotype that gay men are anti-family and averse to monogamy. In line with the exchange theory, participants' exchange of intangible resources, such as trust and effective communication, are associated with their satisfaction and relationship stability.